Public Communication Ethics in Da'wah: A Case Study of Controversial Content by KH. Miftah Maulana Habiburrahman (Gus Miftah) - Handariyatul Masruroh; Afif Mahmudi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Social media has become the main space for preachers (da’i) to convey religious messages to the wider community. However, the communication methods used often trigger various reactions, especially when associated with diverse social and cultural norms. This study analyzes the virality phenomenon of Gus Miftah's sermons, a preacher known for his assertive and outspoken communication style. This study aims to understand the communication strategies used in his preaching and their impact on public opinion. The research method used is qualitative with a case study approach. Data were obtained through content analysis of viral lecture videos and public responses spread across various social media platforms. The results of the study show that the communication carried out by Gus Miftah has its own appeal because of the use of straightforward language and interactive communication style. However, this strategy also sparks debate, especially related to the ethics of communication in Islamic preaching. This study emphasizes that in the digital era, preachers must be wiser in conveying messages in order to remain effective without causing misunderstandings or controversies that can damage the purpose of preaching itself. Therefore, a deeper understanding of media literacy and communication strategies that are in accordance with Islamic values is needed.